The Role of Islamic Religious Education Teachers in Instilling the Values ​​of Religious Moderation in Mojokerto Middle Schools - Moh Fatkhur Rokhzi (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This research has successfully uncovered the pedagogical mechanisms that support the instillation of religious moderation values ​​in Islamic Religious Education (PAI) learning in secondary schools through a multi-site qualitative case study with a touch of classroom ethnography in four fictional schools in Mojokerto. Data were collected through repeated observations, semi-structured interviews with teachers, students, and school management, and analysis of learning documents and digital artifacts. Thematic-comparative analysis shows that the internalization of religious moderation does not rely on a single strategy, but rather on a consistent orchestration: contextual task design that stimulates perspective-taking, strengthening psychological safety with safe language and agreed-upon dialogue rules, mediating differences anchored in shared norms (Pancasila, class rules, the maqashid framework), and formative assessment that assesses the process (active listening, clarifying questions, polite objections). The visible impact is a shift in student language from the right-wrong dichotomy to the reason-impact-context dichotomy, increased equal participation, and the emergence of specific micro-action commitments, especially in online behavior. Variations in device policies, LMS utilization, dormitory culture, and professional collaboration moderate the effectiveness of practices. This study offers a process model linking macro-level religious moderation policies with micro-level practices in PAI classrooms and recommends strengthening training in case-based task design, tension mediation techniques, and process assessment toolkits in teacher professional development and school governance.